Theologian, Teacher, and Friend: Tributes to James M. Gustafson. Issue 1 (29th June 2022) - Childress, James F.; Cahill, Lisa Sowle; Ottati, Douglas F.; Schweiker, William; Boer, Theo A.
Abstract: James M. Gustafson, who died in 2021, has influenced generations of theologians and ethicists. In this article, five students, colleagues, and friends provide short reflections on what Gustafson has meant for their work as scholars of theology and religious ethics.